Differential serum lipid distribution in IPAH and CHD-PAH patients. (January 2022) - Chen, Jingyuan; Rathinasabapathy, Anandharajan; Luo, Jun; Yang, Xiaojie; Luo, Peng; Chen, Yusi; Li, Zilu; Li, Jiang
Abstract: Lipid homeostasis is dysregulated in pulmonary arterial hypertension (PAH). A decrease in serum high- and low-density lipoprotein cholesterol (HDL-C and LDL-C) is significantly associated with the worse prognosis of PAH. However, no study has investigated the differential distribution of lipids in various PAH subtypes. We enrolled 190 patients in this retrospective study, which includes 20 patients with congenital heart disease without PAH (CHD-nonPAH), 101 patients with PAH associated with congenital heart disease (CHD-PAH), 69 patients with idiopathic PAH (IPAH) and 81 healthy controls. Laboratory parameters such as liver and renal function, serum lipids, C-reactive protein, N-terminal pro-brain natriuretic peptide (NT-proBNP), echocardiography, right heart catheterization and 6-min walk distance (6MWD) were performed. All types of cholesterol including HDL-C, LDL-C and total cholesterol (CHOL) were significantly lower in IPAH patients in association with right heart function. Although LDL-C and CHOL were lower in CHD-PAH, they were not associated with disease severity or heart failure. Thus, we conclude that IPAH and CHD-PAH patients exhibited a differential distribution pattern of serum lipids. Highlights: Like other PAH patients, CHD-PAH patients showed a dysregulation in serum lipids. Different serum lipid distribution was found between IPAH and CHD-PAH. Serum HDL-C and total cholesterol were associated with RV function in IPAH patients.